2012
DOI: 10.18388/abp.2012_2077
|View full text |Cite
|
Sign up to set email alerts
|

Salivary proteins in health and disease.

Abstract: Besides their structural catalytic and diverse regulatory functions, proteins are also precursors of many important biological compounds essential for normal functioning of humans. Many of these compounds may be used as markers for identification of specific pathological states. A comprehensive knowledge about the metabolism of salivary proteins and the mechanisms of action of their metabolites allowed the development of effective treatment for many disorders. However, it should not be forgotten that in some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Furthermore, the salivary and blood components used in our model system that are relevant in the clinical context of implant placement are likely an important factor for the profile of initial bacterial attachment. Especially salivary components are known to provide important binding sites for the surface colonization with oral bacteria [67, 68]. The distinct difference in bacterial profiles between UV-treated and untreated titanium was limited to the initial surface attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the salivary and blood components used in our model system that are relevant in the clinical context of implant placement are likely an important factor for the profile of initial bacterial attachment. Especially salivary components are known to provide important binding sites for the surface colonization with oral bacteria [67, 68]. The distinct difference in bacterial profiles between UV-treated and untreated titanium was limited to the initial surface attachment.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, compared with healthy female rats, DB rats showed a significant decrease in saliva production. Previous studies reported that saliva contains several enzymes and serves as a non‐invasive way to measure biologic markers for various systemic as well as oral diseases 15–17 . The identification of specific enzymes (either absent or in abundance) could reveal further information concerning the adverse clinical manifestations associated with xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…Such a close connection between diabetes and oral diseases was explained by the inadequate salivary function in diabetic subjects . Deficiencies in salivary protein content expose mouth and teeth to increased risk of infections . Moreover, the salivary flow reduction can result in clinical dry mouth, which frequently troubles diabetic patients .…”
Section: Introductionmentioning
confidence: 99%